Possible mechanism behind the hard-to-swallow property of oil seed pastes - Rosenthal, Andrew J.; Yilmaz, Seçkin (Taylor & Francis, 2015)
Roasted and crushed oil-rich seeds, such as sesame paste and peanut butter, both share a common structure and elicit an apparent sensation of thickening in the mouth. Working with sesame paste, as an example, the force needed to compress sesame paste:water mixtures peaked at 25% added water. The adhesive force required to pull a plunger from the surface was bimodal with peaks at around 15 and 25% hydration. It is postulated that when introduced to the mouth, water from the saliva is absorbed by the paste leading to a hard, adhesive material that sticks to the palate and the tongue, making these materials hard to swallow. It is hypothesized that the shared hard-to-swallow behaviour exhibited by other oil seed pastes/butters is due to a similar hydration process in the mouth.